2007
DOI: 10.1007/s00424-007-0317-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mitochondria poisoning by FCCP on Ca2+ signaling in mouse skeletal muscle fibers

Abstract: We have studied the effects of mitochondria poisoning by carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP) on Ca(2+) signaling in enzymatically dissociated mouse flexor digitorum brevis (FDB) muscle fibers. We used Fura-2AM to measure resting [Ca(2+)](i) and MagFluo-4AM to measure Ca(2+) transients. Exposure to FCCP (2 microM, 2 min) caused a continuous increase in [Ca(2+)](i) at a rate of 0.60 nM/s and a drastic reduction of electrically elicited Ca(2+) transients without much effect on their decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
3
22
0
1
Order By: Relevance
“…In the companion paper, we have shown that the loss of Ca 2+ from mitochondria determines an increase in the cytosolic Ca 2+ concentration, [Ca 2+ ] i , that rises from less than 100 nM to about 350 nM, measured with Fura-2, not dependent on the presence of external Ca 2+ [8]. Total Fig.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the companion paper, we have shown that the loss of Ca 2+ from mitochondria determines an increase in the cytosolic Ca 2+ concentration, [Ca 2+ ] i , that rises from less than 100 nM to about 350 nM, measured with Fura-2, not dependent on the presence of external Ca 2+ [8]. Total Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, we have shown that poisoning the mitochondria with FCCP causes a slow (0.6 nM/s) increase in the basal myoplasmic [Ca 2+ ] i of mouse fast muscle fibers, with a marked effect on the amplitude of Ca 2+ transients [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevance of SR-mitochondrial Ca 2+ transfer for oxidative metabolism in skeletal muscle When [ATP] was measured using mitochondria-targeted luciferase it was found to be elevated during [Ca 2+ ] m transients that are triggered by membrane depolarization in myotubes, confirming the competence of SR in transferring Ca 2+ to mitochondria to stimulate oxidative metabolism (Jouaville et al, 1999 (Caputo and Bolanos, 2008). Thus, the RyR-mediated mitochondrial transfer of Ca 2+ is relevant for the control of oxidative metabolism and likely allows a local feedback regulation of [Ca 2+ ] c signaling through mitochondria, both in cardiac and skeletal muscle.…”
Section: Mitochondria Camentioning
confidence: 88%
“…En el caso de las mitocondrias, existen diversas evidencias que señalan su contribución a largo plazo en la homeostasis de Ca 2+ de fibras musculares esqueléticas (63,158,159); no obstante, esto no se acepta universalmente. Por su parte, aunque existen pruebas del funcionamiento del intercambiador Na + -Ca 2+ en el músculo esquelético, su papel en el acoplamiento excitación-contracción ha sido poco estudiado (160)(161)(162).…”
Section: Otras Preguntasunclassified